Hubungan antara Work Engagement dengan Turnover Intention pada Pekerja Generasi Milenial di Jabodetabek - Muchtadin, Muchtadin (Jurnal Psikologi Teori dan Terapan, 2022)
This study aims to see the extent to which work involvement is interrelated with turnover intention in millennial generation workers in Jabodetabek. The method used in this research is quantitative. The data analysis technique used descriptive analysis to see the description of the respondents and Pearson correlation analysis was used to see the relationship between the two variables. The sample was taken based on certain criteria, namely workers who were born in 1982 to 2002, worked in Greater Jakarta and had worked for at least one year. Sampling is non-random sampling, namely purposive sampling. A total of 214 millennial workers were collected as respondents. The results of the study found that the data was normally distributed and avoided heteroscedasticity, but the data was not linear, so bootstrapping had to be done. This study concludes that the higher the work engagement, the lower the turnover intention of millennial workers. Future research should limit the type of work to millennial workers in the Jabodetabek area. Companies must determine different strategies in dealing with workers creating millennial generations in order to maintain the work involvement of their workers so as to reduce turnover intention. Penelitian ini bertujuan untuk melihat sejauh mana work engagement saling berkaitan dengan turnover intention pada pekerja generasi milenial di Jabodetabek. Analisis korelasional dipakai untuk melihat hubungan kedua variabel. Sampel diambil berdasarkan kriteria tertentu yaitu pekerja yang lahir di tahun 1982 sampai 2002, bekerja di Jabodetabek dan sudah bekerja minimal selama satu tahun. Pengambilan sampel bersifat non random sampling yaitu purposive sampling. Sebanyak 214 pekerja milenial dikumpulkan sebagai responden. Hasil penelitian menemukan bawah data berdistribusi normal dan terhindar dari heteroskedastisitas namun data tidak linear sehingga harus dilakukan bootstrap. Penelitian ini menyimpulkan bahwa semakin tinggi work engagement maka semakin rendah turnover intention yang dimiliki oleh pekerja milenial. Penelitian selanjutnya harus membatas jenis pekerjaan pada pekerja milenial di wilayah Jabodetabek. Perusahaan harus menetapkan strategi yang berbeda dalam menghadapi pekerja generasi milenial agar dapat mempertahankan work engagement pekerjanya sehingga mengurangi turnover intention.